Dietary diversity and associated factors among people with tuberculosis in Kampala, Uganda: A cross-sectional study - Jonathan Izudi; Simon Kyazze; Francis Bajunirwe (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Rationale.Dietary diversity (DD) is important in enhancing the nutritional status of people with tuberculosis (TB), but has been understudied in Uganda. Objective: To investigate the frequency of adequate DD and the associated factors among people with pulmonary TB aged ≥ 18 years in Kampala, Uganda. Methods: We enrolled people with pulmonary TB across five health facilities in Kampala, Uganda. The outcome variable was adequate DD, assessed using the World Food Program’s Food Consumption Score (FCS). Participants with FCS values < 35 were categorized as having inadequate DD, whereas those with FCS ≥ 35 were classified as having adequate DD. Independent variables included sociodemographic, clinical, and behavioral factors. We used a Generalized Estimating Equation with a Poisson distribution, log link function, and robust standard errors, with health facility as a cluster and several variables to identify the factors associated with adequate DD. We reported adjusted risk ratios (aRR) and 95 % confidence intervals (CI). Results: Of 818 participants studied, 250 (30.6 %) had adequate DD. The factors associated with adequate DD included age ≥ 25 years old (aRR 1.12; 95 % CI: 1.04–1.22), being married (aRR 1.77; 95 % CI: 1.51–2.07), self-employed (aRR 1.22; 95 % CI: 1.09–1.36), and low socioeconomic status (aRR 1.48; 95 % CI: 1.15–1.89). Conclusion: We found a low frequency of adequate DD. Persons aged ≥ 25 years, married, self-employed, and of lower socioeconomic status are more likely to have adequate DD. Findings suggest a complex interplay between socioeconomic factors and DD. Targeted interventions are needed to improve DD among people with TB across different demographic groups.